2023
DOI: 10.3390/genes14061271
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analysis for Resistance to Coniothyrium glycines Causing Red Leaf Blotch Disease in Soybean

Musondolya Mathe Lukanda,
Isaac Onziga Dramadri,
Emmanuel Amponsah Adjei
et al.

Abstract: Soybean is a high oil and protein-rich legume with several production constraints. Globally, several fungi, viruses, nematodes, and bacteria cause significant yield losses in soybean. Coniothyrium glycines (CG), the causal pathogen for red leaf blotch disease, is the least researched and causes severe damage to soybean. The identification of resistant soybean genotypes and mapping of genomic regions associated with resistance to CG is critical for developing improved cultivars for sustainable soybean productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Yet, understanding the complexity of inheritance governing resistance is crucial for successful breeding programs [46]. Evaluation of the panel of lines can be linked with diseases affecting soybeans, such as sudden death syndrome, bacterial leaf pustule, rust, and red leaf blotch disease [26,[47][48][49]. However, there is no similar study conducted on red crown disease to date.…”
Section: Evaluation and Identification Of Resistance To Soybean Red C...mentioning
confidence: 99%
“…Yet, understanding the complexity of inheritance governing resistance is crucial for successful breeding programs [46]. Evaluation of the panel of lines can be linked with diseases affecting soybeans, such as sudden death syndrome, bacterial leaf pustule, rust, and red leaf blotch disease [26,[47][48][49]. However, there is no similar study conducted on red crown disease to date.…”
Section: Evaluation and Identification Of Resistance To Soybean Red C...mentioning
confidence: 99%
“…Several phytopathogenic diseases are known to limit legume productivity [ 41 , 42 ]. For example, soybean rust [ 43 ], soybean stay-green disease [ 44 ], soybean red leaf blotch disease [ 45 ], pea blight disease [ 45 ], peanut rust [ 46 ], peanut leaf spot [ 47 ], faba bean root rot [ 48 ], and other legume pathogenic diseases are caused by multiple pathogens and are responsible for severe yield loss. Reports have also demonstrated that the productivity of legume crops such as soybeans, chickpeas, and peanuts has been inhibited by different abiotic stresses [ 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%